The Influence of Spiritual Intelligence on Students' Learning Motivation (Survey at SMA Negeri 103 Jakarta) - Nahuda*, Nahuda; Nurhasanah, Nurhasanah; Nadiah, Nadiah (Riwayat: Educational Journal of History and Humanities, 2023)
This research is motivated by the conditions of education which are still not in line with expectations as a generation that is intelligent and has attitudes that can be implemented in society. With this spiritual intelligence it is hoped that it can be successful and realize national education goals. One of the goals of national education is to have religious spiritual strength, self-control, personality, intelligence, noble morals, and the skills needed by oneself, society, nation and state. This can be realized when children have religious knowledge that can be practiced in their environment. Therefore, with the motivation to learn within him, it is hoped that he will be able to produce output that is in accordance with national education goals. This research aims to obtain precise, correct, valid and reliable data regarding the influence of spiritual intelligence on student learning motivation at SMA Negeri 103 Jakarta. The magnitude of the influence is said to be strong or high. The method used in this study uses the quantitative correlation method. Using the Simple Random Sampling method, there were 42 students at SMA Negeri 103 Jakarta, and equipped with data collection techniques, observation, documentation, interviews. While in analyzing using product moment correlation technique. The research results show that if you look at the Product Moment coefficient test, it produces "rxy" or "ro" of 0.854, while "rt" in the table is significant at 5% = 0.308 and at a significance level of 1% = 0.398. Thus it can be seen that "ro" "rt" is significant at both 5% and 1%. So based on these results the Alternative Hypothesis (Ha) is accepted or approved and the Null Hypothesis (Ho) is rejected or not approved. Based on this research, it can be concluded that there is an influence on spiritual intelligence on students' learning motivation at SMA Negeri 103 Jakarta.